Solve the factored quadratic equation 0=−\(\frac{1}{3}x\)(x−6)

.(1 point)

1 answer

To solve the factored quadratic equation \(0 = -\frac{1}{3}x(x - 6)\), we can set each factor equal to zero.

  1. Set the first factor equal to zero: \[ -\frac{1}{3}x = 0 \] Multiplying both sides by -3 to eliminate the fraction gives us: \[ x = 0 \]

  2. Set the second factor equal to zero: \[ x - 6 = 0 \] Adding 6 to both sides gives us: \[ x = 6 \]

Thus, the solutions to the equation \(0 = -\frac{1}{3}x(x - 6)\) are: \[ x = 0 \quad \text{and} \quad x = 6 \]